Recruiting women to work in the Kingdom of Saudi Arabia : challenges in leadership and cultural intelligence - Elliott, Jacquelyn D.; DeFrank-Cole, Lisa (London : SAGE Publications: SAGE Business Cases Originals, 2018)
This case illuminates the challenges faced in recruiting women to work in the Kingdom of Saudi Arabia (KSA), even for a brief assignment. Despite the fact women work abroad far less often than their male counterparts - and that working abroad is a desirable leadership competency -recruiting women to work in certain regions of the world is more challenging than others, and may create an ethical dilemma for the recruiter. The case further highlights the advancing role of women in higher education in the KSA. Ultimately, the case encourages students to process the political landscape surrounding international job opportunities, the role gender plays, and how the rejection of such opportunities can hinder job advancement.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Women -- Employment -- Saudi Arabia; Employment in foreign countries